Evaluation of the coronary flow by the coronary clearance time in patients with cardiac syndrome X. Issue 3 (March 2018) - Yildirim, Erkan; Yuksel, Uygar Cagdas; Celik, Murat; Bugan, Baris; Gungor, Mutlu; Gokoglan, Yalcin; Koklu, Mustafa; Gormel, Suat; Yasar, Salim; Barcin, Cem
Objective: The vessels involved in the microcirculation are too small to be visualized by conventional angiography and no tools are currently available that can directly evaluate the coronary microcirculation. This study evaluated the coronary clearance frame count (CCFC) in patients with cardiac syndrome X (CSX). Methods: The retrospective study enrolled patients with angina, who had a positive nuclear imaging test and normal coronary angiography; and a control group consisting of patients who underwent an angiogram to exclude coronary artery disease. Thrombosis in myocardial infarction frame count (TFC) and CCFC for each coronary artery (left anterior descending coronary artery [LAD], circumflex coronary artery [CFX] and right coronary artery [RCA]) were calculated offline. Results: A total of 71 patients with CSX and 61 control patients were enrolled in the study. No significant differences were found between the two groups regarding the baseline demographic and clinical variables. The TFC of LAD, CFX and RCA were similar between the two groups. The mean CCFC-LAD, CCFC-CFX and CCFC-RCA were significantly longer in the CSX group compared with the control group. Conclusion: CCFC is a simple, quantitative and highly reproducible method that might be used as a marker of coronary microvascular dysfunction.